Margaret cavendish, Duchess of Newcastle : (Cambridge University Press, 2003)
Margaret Cavendish, Duchess of Newcastle (1623-1673) is unique among women writers of the seventeenth century in the scale of her output and in her aspiration to create a philosophical system. This edition presents Cavendish as a political author, and Susan James includes two major texts, the Orations and The Blazing World, accompanied by the standard series features that enables students to gain a better understanding of one of the truly distinctive political voices of the early modern period.